2021
DOI: 10.1093/nutrit/nuab070
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between abdominal obesity (based on waist circumference) and serum vitamin D levels: a systematic review and meta-analysis of epidemiologic studies

Abstract: Context Although previous observational studies have investigated the association between waist circumference (WC) values and serum vitamin D levels, findings have been inconsistent. Objective A systematic review and meta-analysis was performed to evaluate the effect of abdominal obesity (based on WC) on vitamin D deficiency or insufficiency in adults. Data Sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 53 publications
2
8
1
1
Order By: Relevance
“…In our cohort, 25(OH)D demonstrated negative correlation with waist circumference and abdominal fat mass. This data is in agreement with findings from recent meta-analysis of epidemiologic studies indicating an association between vitamin D deficiency and abdominal obesity[ 46 ]. Vitamin D deficiency in obese people is attributed to lower dietary intake of vitamin D, lesser skin exposure to sunlight, decreased vitamin absorption, impaired hydroxylation in adipose tissue and 25(OH)D accumulation in fat[ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our cohort, 25(OH)D demonstrated negative correlation with waist circumference and abdominal fat mass. This data is in agreement with findings from recent meta-analysis of epidemiologic studies indicating an association between vitamin D deficiency and abdominal obesity[ 46 ]. Vitamin D deficiency in obese people is attributed to lower dietary intake of vitamin D, lesser skin exposure to sunlight, decreased vitamin absorption, impaired hydroxylation in adipose tissue and 25(OH)D accumulation in fat[ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…25-hydroxyvitamin D [25(OH)D], the main form of circulating vitamin D, is widely applied as an indicator of vitamin D status. It is now well demonstrated that vitamin D also plays a role in many extra-skeletal health issues [ 2 ], such as metabolic syndrome (MetS) [ 3 , 4 ], type 2 diabetes mellitus (T2DM) [ 5 ], abdominal obesity [ 6 , 7 ], hypertension [ 8 , 9 ], and dyslipidemia [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this systematic review showed that vitamin D may play a positive role in improvement of COVID‐19 clinical outcomes. It seems that antioxidative, antiinflammatory, and immunomodulatory properties of vitamin D can be involved in this regard (Hajhashemy et al, 2022 ; Musavi et al, 2020 ). Besides, some researchers discussed the key role of vitamin D in the RAS (Kumar et al, 2020 ; Malek Mahdavi, 2020 ; Musavi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%